Conculcación de derechos constitucionales en el debido proceso por omisión de motivación del juez de segunda instancia. - Asanza Enderica, Carlos Roberto (2018)
The present titling work is focused on determining if the rights of the appellant were violated in the due process, for the omission of the motivation in the sentence issued by the administrators of justice in the process that is substantiated by the protective action signed with the N.- 13956-2012-0540 and filed the appeal in second instance was rejected confirming the ruling issued by the judge of first instance. The facts are inferred from the moment that the plaintiff, lending his services as a collector in the National Electricity Corporation, was prevented from entering his place of work, on June 8, 2012, by means of an office, a thank you was extended. for the years worked in the institution, it is worth mentioning that his occasional work contract was still in force, it is important to clarify that he had a hearing disability of 39% and that he was exercising his right to breastfeeding, rights recognized in the constitution. also the other norms that govern us as is the organic law of public service and respective regulations, and the international instruments ratified by Ecuador. In this case, serious violations of the rights enshrined in our constitutional text arise, and more of them enshrine guarantees that should be the appropriate mechanisms to protect these rights, but that personal interests are shown to be violated in this way.